Teaching Children’s Motor Skills for Team Games Through Guided Discovery: How Constraints Enhance Learning - Newell, Karl M.; Rovegno, Inez (Frontiers in Psychology, 2021)
In this paper we examine the role of instructional strategies as constraints within a 22 discovery learning framework for the teaching of open skill team ball games to elementary 23 school-aged children. The cohesive and adaptive integration of constraints (individual, 24 environment, and task) by practitioners of movement and physical activity (instructor, teacher, 25 coach) is proposed as the pathway to exploiting the effectiveness of guided discovery learning. 26 The qualitative analysis of the practical instantiations of this framework by expert teachers is 27 examined with respect to the learning of open skill team invasion games (e.g., basketball, 28 soccer). The primary constraints to action in this learning-teaching developmental framework 29 are coordinated so as to keep the self-organization of skill development (movement pattern and 30 tactics) continually evolving, while preserving the child’s motivation and enjoyment for the 31 expanding repertoire and performance capacity of his/her perceptual-motor skills. In this open 32 skill and elementary school age-related context, generality and specificity are both necessary and 33 complementary in the expression of task, skill and practice influences on motor learning and 34 performance